DEVELOPMENT OF THE SAKINAH FAMILY MODULE WITH A MULTICULTURAL PERSPECTIVE IN THE YOGYAKARTA MGBK COMMUNITY - Falah, Nailul (PABKI (Perkumpulan Ahli Bimbingan dan Konseling Islam) Indonesia, 2024)
Pre-marital education cannot be said to be optimal because at KUA it is delivered in very little time and in schools with a very limited range of students and materials. Apart from that, so far the concept of premarital education has mostly been interpreted from a religious perspective, but the concept of sakinah actually also exists and lives in a multicultural context. Therefore, a sakinah family module with a multicultural perspective is needed as material for students to increase their insight into marriage.From the results of the research and development carried out, the module has been successfully developed. The resulting module has been tested. The measurement results show that it was carried out on 30 respondents. The average results obtained at the pre-test were 6.933 and at the post-test 9.22. These results are then continued with paired t test analysis which will be discussed in the evaluation, summative section. The results above show that a sig value of 0.001 which is smaller than 0.05 means significant. The second confirmation is the t test value of 8.366 which is greater than the t table which shows that there is a difference in insight between after and before the test was carried out.